PERANCANGAN SISTEM KONTROLER ALAT ELEKTRONIK RUMAH TANGGA BERBASIS MIKROKONTROLER ARDUINO UNO DENGAN PERINTAH SUARA - saftiadi .; A Asni B; aswadul fitri saiful rahman (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2019)
The operation of electronic equipment in general is still manual or semi-automatic that uses a remote or switch around thetool area. With the development of increasingly sophisticated technology and information science, electronic equipment that is athome we can easily control remotely if we want to do it with a specific purpose and purpose. In daily life, we can apply the conceptof a smart home, which can control electronic equipment in our homes using Voice activation. So it can turn on or turn off electronicdevices inside our homes by using a web server or an android smart phone, with the condition that it is connected with Bluetooth foraccess control. The basis of this system can also be called Voice Activation. In making this tool the author uses the Arduino Unomicrocontroller, using Bluetooth HC-06 / HC-05 module, 4x 330 Ohm resistor, 4x Color LED, jumper cable and Android smartphone.This tool can control the electronic equipment that is in our homes by using an Android smart phone that has the application installed, thecontrol connection uses Bluetooth, as access control